Adverse outcome pathways potentially related to hazard identification of microplastics based on toxicity mechanisms. (September 2019) - Jeong, Jaeseong; Choi, Jinhee
Abstract: Increasing concern over microplastics has recently brought increased attention to studies on microplastic toxicity. Here, we conduct a systematic review on toxicity of microplastics that focuses on identifying data gaps in the mechanisms of microplastic toxicity. We observe that microplastic toxicology research thus far has focused on ecotoxicity using apical endpoints and only a few studies deal with toxicity mechanisms. Based on this review, we propose putative Adverse Outcome Pathways (AOPs) applicable to microplastic management to understand microplastic toxicity. We matched toxicity mechanisms and apical endpoints to a key event (KE) and adverse outcome (AO) information from the AOP Wiki. Overall, our results suggest that the molecular initiating event (MIE) was reactive oxygen species (ROS) formation and the AO was increased mortality, decreased growth and feeding, and reproduction failure. However, there are a limited number of studies on toxicity mechanisms of microplastics and, therefore, evidence concerning the relationship between KEs is not sufficient. Clearly, more studies on toxicity mechanisms are required to fill these gaps in data. This study also suggests that the AOP framework is a suitable tool to integrate existing data from various literature sources and can identify data gaps in microplastic toxicity mechanisms. Graphical abstract: Image 1 Highlights: Microplastic toxicity mechanisms in terms of ecotoxicity and human health toxicity were reviewed. Microplastic toxicology research has focused on ecotoxicity using apical endpoints. Toxicity mechanisms matched with KE from the AOP Wiki and putative AOPs were proposed. MIE is ROS formation and AOs are increasing mortality, reduction of growth, and reproduction failure.